Codification de la terminologie juridique dans les définitions légales - Petrů Ivo (Echo des Etudes Romanes, 2015)
This study examines the interaction between the language and law in the drafting of legal norms. More specifically, it deals with the codification of legal terms in legal definitions, exploring the processes used by a legislator in their creative work. After a brief reminder of the Linguistic-Circle-of-Prague theory concerning the subject, this study proposes a certain typology of legal definitions and focuses on the linguistic analysis of specific examples. These are taken from the New Czech Civil Code, which came into force in 2014.